VICTIMLESS CRIMINAL ARRANGEMENTS: A REVIEW OF MORALITY CRIMES - Nemos Muhadar (Faculty of Law, Universitas Pekalongan, 2023)
Criminal law without victims is a legal concept that focuses on the restoration of social harm and the protection of societal values, rather than solely addressing individual harm. Acts of indecency involve behaviors that violate social norms without directly affecting physical or economic victims. The regulation of victimless crimes in the context of decency laws is relevant to changes in societal behavior and modern technology, but it also raises questions about the balance between protecting societal values and individual freedoms. This research aims to evaluate the regulation of victimless crimes in the context of decency laws in Indonesia and analyze the impact of implementing these regulations on modern society. The study employs normative research methods to analyze the relevant legal regulations concerning victimless crimes in the context of decency. Data will be collected through literature reviews, including online and printed legal sources, with the goal of providing valuable recommendations for policymakers and legal practitioners addressing issues related to victimless crimes in decency. The research findings highlight that in Indonesia, the regulation of victimless crimes in the context of decency includes laws aimed at preserving the morality and decency of society as a whole without requiring individual victims who feel harmed. Examples of such laws include the Pornography Law, Gambling Regulation, and Child Protection Law. While these laws protect moral values, they can also pose threats to individual freedoms, necessitating ongoing evaluation to strike the right balance. The implementation of these regulations in modern society has complex impacts, including on individual human rights, legal effectiveness, social norms, culture, and government-citizen relations. Achieving a balance between safeguarding individual human rights and regulating behavior perceived as harmful to society is crucial in the development of modern society.